2021
DOI: 10.3389/fcell.2021.660159
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin-Like 3 Enhances Invasion and Metastasis via β-Catenin-Mediated EMT and Aerobic Glycolysis in Colorectal Cancer

Abstract: Previous studies reported that Follistatin-like 3 (FSTL3) is abundantly expressed in several solid tumors and participate in the regulation of cell metabolism. However, the clinico-pathological significance, biological role and molecular mechanism of FSTL3 in colorectal cancer (CRC) is still unclear. Here we report that the expression level of FSTL3 in colon cancer specimens was significantly higher, compared to normal tissue and interestingly, the expression of FSTL3 was related to lymph node metastasis, tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 54 publications
(66 reference statements)
3
43
0
Order By: Relevance
“…22 Epithelial-mesenchymal transition (EMT) exerts crucial functions in the process of tumor metastasis and invasion, including breast cancer, thyroid cancer, and colon cancer. [23][24][25] EMT refers to the process of cell remodeling characterized by migratory and invasive abilities through epithelial cells upon multiple physiological and pathological stimuli. 26 The promoting effects of EMT on HBV-related HCC progression have been suggested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Epithelial-mesenchymal transition (EMT) exerts crucial functions in the process of tumor metastasis and invasion, including breast cancer, thyroid cancer, and colon cancer. [23][24][25] EMT refers to the process of cell remodeling characterized by migratory and invasive abilities through epithelial cells upon multiple physiological and pathological stimuli. 26 The promoting effects of EMT on HBV-related HCC progression have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LINC01352 dysregulation enhances HBV‐related HCC by targeting miR‐135b 22 . Epithelial‐mesenchymal transition (EMT) exerts crucial functions in the process of tumor metastasis and invasion, including breast cancer, thyroid cancer, and colon cancer 23–25 . EMT refers to the process of cell remodeling characterized by migratory and invasive abilities through epithelial cells upon multiple physiological and pathological stimuli 26 .…”
Section: Introductionmentioning
confidence: 99%
“…5A , most of the molecules in this signaling pathway have a significant relationship with the EMT phenotype. The analysis of the interaction network indicated that ADAM12 may interact with FSTL3 to potentially promote the metastasis and EMT phenotype of tumors ( 41 , 42 ). Therefore, we constructed stable ADAM12 overexpression AGS cells and knockdown HGC27 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the protein-protein interaction network revealed that follistatin like 3 (FSTL3) may be a potential partner of ADAM12. Previous studies have emphasized that FSTL3 can enhance tumor cell metastasis ( 41 , 42 ) and the polarization of macrophages and fibroblasts by forming an inhibitory immune microenvironment ( 47 ). Therefore, it is clear that ADAM12 and FSTL3 perform similar functions, which may imply a mutual adjustment relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprogramming, known as the Warburg effect, is characterized by enhanced glycolytic activity and lactate fermentation in cancer ( Warburg, 1956 ; Li et al, 2021 ). Tumor cells rewire metabolic pathways to supply energy and increase tolerance to an oxygen-deficient environment ( Li et al, 2021 ). The connections between aerobic glycolysis and EMT are not well-understood.…”
Section: Discussionmentioning
confidence: 99%